ANALISIS STANDAR MANAJEMEN INSTALASI LABORATORIUM MEDIS RUMAH SAKIT X PEKANBARU TAHUN 2025 - Muhammad Dedi widodo; Nizma Khairunissa; Reno Renaldi; Aldiga Rienarti Abidin; Ahmad Satria Efendi; Welly Sando (Journal of Hospital Administration and Management (JHAM), 2025)
The Laboratory Installation is a supporting unit that plays an important role in clinical diagnosis through specimen examination. This study aims to analyze the management standards of the Medical Laboratory Installation at X Hospital Pekanbaru in 2025 based on four aspects: human resources, facilities, infrastructure, and standard operating procedures. This qualitative research used a descriptive approach through in-depth interviews and observations involving six informants (medical support service manager, laboratory analysts, unit head, and patients). The results showed that the number of laboratory analysts was insufficient to support 24-hour services, resulting in high workloads and multitasking. This condition is influenced by limited hospital funding due to a decrease in patient visits to the laboratory. In terms of facilities, the laboratory lacked essential equipment in accordance with standards, such as an autoclave, biosafety cabinet, and spectrophotometer, and quality control was not carried out routinely. Regarding infrastructure, deficiencies were found in active protection systems such as hydrants, automatic sprinklers, and evacuation routes, as well as the absence of accessibility facilities for persons with disabilities. This is due to the laboratory being located in an old building not designed according to current technical standards. Although standard operating procedures are available, their implementation remains suboptimal, as some staff members do not fully use personal protective equipment, and several work processes are still conducted manually. It is recommended that the hospital increase budget allocation proportionally to hire more analysts, complete laboratory equipment, conduct gradual infrastructure renovations focusing on safety and accessibility, and strengthen supervision, monitoring, and evaluation—while enforcing discipline for staff who fail to comply with PPE protocols—to ensure safety and service quality in the laboratory.